2014
DOI: 10.1212/wnl.0000000000000497
|View full text |Cite
|
Sign up to set email alerts
|

Novel (ovario) leukodystrophy related to AARS2 mutations

Abstract: Objectives: The study was focused on leukoencephalopathies of unknown cause in order to define a novel, homogeneous phenotype suggestive of a common genetic defect, based on clinical and MRI findings, and to identify the causal genetic defect shared by patients with this phenotype.Methods: Independent next-generation exome-sequencing studies were performed in 2 unrelated patients with a leukoencephalopathy. MRI findings in these patients were compared with available MRIs in a database of unclassified leukoence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
178
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(193 citation statements)
references
References 22 publications
(28 reference statements)
12
178
0
Order By: Relevance
“…Most YARS2 defects result in a more moderate MLASA2 than seen in the patient mentioned above (Riley et al 2013;Shahni et al 2013); however another lethal infantile case has recently been reported (Nakajima et al 2014). In the case of AARS2, two missense variants have been associated with a lethal infantile cardiomyopathy (Gotz et al 2011), while another 11 variants have resulted in leukoencephalopathy and premature ovarian failure (Dallabona et al 2014). A range of compound heterozygous variants in EARS2 result in leukoencephalopathy with thalamus and brainstem involvement and high lactate (Steenweg et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most YARS2 defects result in a more moderate MLASA2 than seen in the patient mentioned above (Riley et al 2013;Shahni et al 2013); however another lethal infantile case has recently been reported (Nakajima et al 2014). In the case of AARS2, two missense variants have been associated with a lethal infantile cardiomyopathy (Gotz et al 2011), while another 11 variants have resulted in leukoencephalopathy and premature ovarian failure (Dallabona et al 2014). A range of compound heterozygous variants in EARS2 result in leukoencephalopathy with thalamus and brainstem involvement and high lactate (Steenweg et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…However, in other cases, different mutations in the same gene result in distinct phenotypes. For example, AARS2 mutations result in either infantile cardiomyopathy (OMIM 614096) (Gotz et al 2011) or leukoencephalopathy with premature ovarian failure (POF; OMIM 615889) (Dallabona et al 2014). In this study we expand the clinical spectrum associated with LARS2 variants to include a patient with hydrops, lactic acidosis, sideroblastic anemia, and infantile multisystem failure.…”
Section: Introductionmentioning
confidence: 99%
“…Recessive variants in AARS2 were associated with leukoencephalopathy and POI in six subjects (MIM 615889) (68). Subjects had childhood onset of neurological deterioration including ataxia, spasticity, cognitive decline and white matter abnormalities.…”
Section: Variants In Nuclear Genes Encoding Mitochondrial Proteinsmentioning
confidence: 99%
“…2 0 1 2 ) ; E A R S 2 (OMIM#614924) (Steenweg et al 2012) and AARS2 (OMIM#615889) (Dallabona et al 2014). Although the biochemical signatures and neuroimaging of combined respiratory chain deficiency can be distinctive, it remains difficult to infer the genetic origin from often heterogeneous phenotypes.…”
Section: Introductionmentioning
confidence: 99%